2018
DOI: 10.1016/j.jphs.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic preconditioning but not ketamine reduces oxygen and glucose deprivation induced neuronal injury correlated with downregulation of COX-2 expression in mouse hippocampal slices

Abstract: Hypothermic preconditioning is an effective treatment for limiting ischemic injury, but the mechanism is poorly understood. This study was aimed to explore the effect of hypothermic and ketamine preconditioning on oxygen and glucose deprivation (OGD) induced neuronal injury in mouse hippocampal slices, and to investigate its possible mechanism. The population spike (PS) was recorded in the CA1 region of mouse hippocampal slices using extracellular recordings, Na/K ATPase activity in slices was determined by sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Contradictory to the findings that detected slower changes of brain diffusivity in AQP4 −/− during acute ischemia in vivo (Yao et al, 2015;Hirt et al, 2017;Chmelova et al, 2019), we did not observe a similar influence of AQP4 deletion during OGD in situ (Chmelova et al, 2019). This could be associated with the previously seen protective effect of hypothermic (32-33 • C) preconditioning that is present in situ (Jiang et al, 2018;Kreisman et al, 2020). Moreover, we previously demonstrated that severe pathological conditions are needed to reveal the role of AQP4 in cell swelling (Dmytrenko et al, 2013;Anderova et al, 2014).…”
Section: The Simultaneous Deletion Of Aqp4 and Trpv4 Block Changes Of...contrasting
confidence: 69%
“…Contradictory to the findings that detected slower changes of brain diffusivity in AQP4 −/− during acute ischemia in vivo (Yao et al, 2015;Hirt et al, 2017;Chmelova et al, 2019), we did not observe a similar influence of AQP4 deletion during OGD in situ (Chmelova et al, 2019). This could be associated with the previously seen protective effect of hypothermic (32-33 • C) preconditioning that is present in situ (Jiang et al, 2018;Kreisman et al, 2020). Moreover, we previously demonstrated that severe pathological conditions are needed to reveal the role of AQP4 in cell swelling (Dmytrenko et al, 2013;Anderova et al, 2014).…”
Section: The Simultaneous Deletion Of Aqp4 and Trpv4 Block Changes Of...contrasting
confidence: 69%
“…In addition, an increased amount of Ni 2 O 3 has been reported to contribute to an increased work function (WF) . The peaks at 531.7 and 532.1 eV are related to NiOOH. The higher binding energy at 533 eV is attributed to hydroxyl (OH) groups, and the intensity of this peak increases after the treatment, which is probably because of the hydroxyl group present in the MeO-2PACz structure.…”
Section: Resultsmentioning
confidence: 99%
“…A brief cycle of HP applied before an ischemia-reperfusion episode significantly decreased both damage and oxidant indicators while increasing antioxidant levels in isolated perfused rat liver [30]. Jiang et al (2018) showed that the downregulation of COX-2 expression and the increase of Na + /K + ATPase activity increase tolerance to hypoxic damage and may be associated with the effectiveness of mild HP at 33 °C [31]. These results show that HP might be a promising strategy in protecting the brain against hypoxic damage.…”
Section: Discussionmentioning
confidence: 99%